What are The Most Effective Management Strategies for Obstetric Emergencies in ICU Settings, and How do They Impact Maternal and Neonatal Mortality Rates? : A Systematic Review - Landong Sijabat; Raka Jati Prasetya; Mutia Juliana (The Indonesian Journal of General Medicine, 2026)
Background: Obstetric emergencies requiring intensive care unit (ICU) admission contribute significantly to maternal and neonatal mortality worldwide, yet optimal management strategies remain heterogenous across settings. Methods: This systematic review synthesized 80 studies (1990-2025) examining management strategies for obstetric emergencies in ICUs. Outcomes included maternal mortality, neonatal mortality, and effectiveness of interventions. Results: Hypertensive disorders (42.96% in Africa) and hemorrhage (24.15%) were the leading admission causes. Multidisciplinary team approaches, early intervention (<6 hours for hemorrhage), and protocolized care consistently improved outcomes. Whole blood transfusion reduced transfusion volumes versus component therapy (2,607 mL vs. 4,683 mL, p=0.03) with zero maternal deaths. The non-pneumatic antishock garment combined with balloon tamponade eliminated hemorrhage-related mortality (0% vs. 3 deaths). Continuous renal replacement therapy reduced sepsis mortality by 35%. Skills training for postpartum hemorrhage reduced maternal mortality from 75% to 0%. Maternal mortality ranged from 0%-41.2%, with African centers reporting 30.69% versus 3.03% in dedicated obstetric ICUs. Neonatal mortality ranged 4.2%-52%. Critical timing factors included ICU admission <24 hours from symptom onset and delivery before critical deterioration. Discussion: Effective management requires condition-specific, early, multidisciplinary approaches. Resource disparities explain much outcome variation, with unbooked status and delayed referral as key modifiable risk factors. Standardized protocols, early warning systems, and uterine-conserving techniques show strongest evidence. Conclusion: Early, protocol-driven, multidisciplinary ICU management significantly reduces maternal and neonatal mortality in obstetric emergencies. System strengthening and skills training are as crucial as technological interventions.